Polymeric electro-dry-adhesives for use on conducting surfaces. (April 2014) - Krahn, JM; Pattantyus-Abraham, AG; Menon, C
This work presents electro-dry-adhesives, designed for use on conducting surfaces, that synergistically combine biomimetic dry adhesives with mushroom-like fibres and embedded conductive polymer electrodes. Together, the dry-adhesive surface and electrodes enable the electro-dry-adhesives to generate greatly improved shear adhesion bond strengths. The electro-dry-adhesives described in this work are fabricated with a poly(dimethylsiloxane) biomimetic dry-adhesive surface and embedded interdigitated electrodes manufactured from a carbon black and poly(dimethylsiloxane) composite conductive polymer. The poly(dimethylsiloxane) dry-adhesive layer allows the electro-dry-adhesives to be used both passively and actively, and the poly(dimethylsiloxane) acts as a dielectric insulator between the electrodes and enables the electro-dry-adhesive to be used on conducting surfaces. In order to compare both passive and active use of the electro-dry-adhesives, shear adhesion bond strength is measured and compared with voltage potentials from 0 kV up to 3 kV applied across the electrodes with up to a 2.56 times increase in shear adhesion bond strength. The increase in shear adhesion bond strength due to the generation of an induced electrostatic attractive force is compared to the theoretical maximum shear adhesion bond strength at each of the voltages applied.